Microstructural alterations in the locus coeruleus‐entorhinal cortex pathway in Alzheimer's disease and frontotemporal dementia - Quattrini, Giulia; Pini, Lorenzo; Boscolo Galazzo, Ilaria; Jelescu, Ileana O.; Jovicich, Jorge; Manenti, Rosa; Frisoni, Giovanni B.; Marizzoni, Moira; Pizzini, Francesca B.; Pievani, Michela (Alzheimer's & dementia : diagnosis, assessment & disease monitoring, 2024)
INTRODUCTION We investigated in vivo the microstructural integrity of the pathway connecting the locus coeruleus to the transentorhinal cortex (LC‐TEC) in patients with Alzheimer's disease (AD) and frontotemporal dementia (FTD). METHODS Diffusion‐weighted MRI scans were collected for 21 AD, 20 behavioral variants of FTD (bvFTD), and 20 controls. Fractional anisotropy (FA), mean, axial, and radial diffusivities (MD, AxD, RD) were computed in the LC‐TEC pathway using a normative atlas. Atrophy was assessed using cortical thickness and correlated with microstructural measures. RESULTS We found (i) higher RD in AD than controls; (ii) higher MD, RD, and AxD, and lower FA in bvFTD than controls and AD; and (iii) a negative association between LC‐TEC MD, RD, and AxD, and entorhinal cortex (EC) thickness in bvFTD (all p < 0.050). DISCUSSION LC‐TEC microstructural alterations are more pronounced in bvFTD than AD, possibly reflecting neurodegeneration secondary to EC atrophy. Highlights Microstructural integrity of LC‐TEC pathway is understudied in AD and bvFTD. LC‐TEC microstructural alterations are present in both AD and bvFTD. Greater LC‐TEC microstructural alterations in bvFTD than AD. LC‐TEC microstructural alterations in bvFTD are associated to EC neurodegeneration.